Redefining maladaptation to climate change: a conceptual examination of the unintended consequences of adaptation strategies on ecological-human systems - Rouzaneh, Davoud; Savari, Moslem (Frontiers in Forests and Global Change, 2024)
This study presents a redefinition of maladaptation to climate change, offering a comprehensive analysis through qualitative content analysis with an inductive approach, supported by focus group discussions. The main goal was to uncover the conceptual dimensions of the unintended and negative impacts of adaptation strategies on socio-ecological systems, particularly forests and natural resources. The findings indicate that some adaptation measures, though initially aimed at mitigating climate change effects, can paradoxically exacerbate long-term vulnerability, leading to environmental degradation and a diminished adaptive capacity of these systems. In response to these outcomes, the study offers strategic recommendations for managing maladaptation risks. These include adopting integrated adaptation management practices, fostering participatory policymaking, and leveraging local knowledge to enhance both social and ecological resilience. By highlighting the critical need to recognize maladaptation’s potential, this research equips policymakers and natural resource managers with insights into the unintended consequences of adaptation efforts, enabling them to craft more effective strategies for climate resilience.